Analisis Food Photography UMKM Mini Dessert Box - Wulandari; Alberd, Ahmad; Azhar, Fahrul (Magenta | Official Journal STMK Trisakti, 2022)
With the expansion of the food industry, business owners must become more careful of the photographs that are shared on social media. There are many good food images in composition and viewpoint that may be taken with simply a smartphone. Several brands have come to our attention among the various SME producers to study the images of their food products. The qualitative study method was utilized to examine images of numerous SME brands, particularly those selling dessert boxes, to see how the composition and angle were utilised. When photographing dessert boxes for promotional purposes, this study is expected to serve as a guide for photographers, particularly those who specialize in food photography.